ChemInform Abstract: Fe+3‐Montmorillonite K‐10 as a Green and Reusable Catalyst for the Synthesis of New Generation of Dihydropyrimidinones. Issue 19 (18th April 2013) - Nikpassand, Mohammad; Fekri, Leila Z.; Gharib, Maryam; Marvi, Omid
Abstract via a simple Biginelli protocol; 8 examples